2014
DOI: 10.1021/mp500498e
|View full text |Cite
|
Sign up to set email alerts
|

Physical Stability of the Amorphous Anticholesterol Agent (Ezetimibe): The Role of Molecular Mobility

Abstract: The purpose of this paper is to examine the role of molecular mobility in the recrystallization process from the amorphous state of the anticholesterol drug ezetimibe. Both the molecular dynamics and crystallization kinetics have been studied using various experimental techniques, such as broadband dielectric spectroscopy (BDS), differential scanning calorimetry (DSC), and X-ray diffraction (XRD). Our investigations have shown that ezetimibe easily recrystallizes from the disordered state, both below and above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 47 publications
(92 reference statements)
7
68
0
Order By: Relevance
“…Knapik et al have shown that the physical stability and water solubility of the amorphous drug (ezetimibe) were improved over 6 times when mixed within a PASD using Soluplus® as carrier. 125 DSC and dielectric spectroscopy analysis of amorphous ezetimibe have led to the conclusion that the high molecular mobility, reflected in structural relaxation, is mainly responsible for its high crystallization tendency. This indicates that formation of a PASD in the Sol-uplus® matrix acts as physical barrier to the molecular motions of glass ezetimibe leading to improved stability.…”
Section: Reduction Of Molecular Mobility Of Amorphous Drug In Pasdmentioning
confidence: 99%
“…Knapik et al have shown that the physical stability and water solubility of the amorphous drug (ezetimibe) were improved over 6 times when mixed within a PASD using Soluplus® as carrier. 125 DSC and dielectric spectroscopy analysis of amorphous ezetimibe have led to the conclusion that the high molecular mobility, reflected in structural relaxation, is mainly responsible for its high crystallization tendency. This indicates that formation of a PASD in the Sol-uplus® matrix acts as physical barrier to the molecular motions of glass ezetimibe leading to improved stability.…”
Section: Reduction Of Molecular Mobility Of Amorphous Drug In Pasdmentioning
confidence: 99%
“…Similar behavior was previously observed in the case of ezetimibe, celecoxib and sildenafil. 20,21,22,23 Figure 1 presents dielectric spectra collected at temperatures below T g . In this temperature region the structural relaxation becomes too slow to be observed and only secondary relaxation processes may be visible.…”
Section: Molecular Dynamics Of Pure Nimesulide Above and Below The Glmentioning
confidence: 99%
“…Molecular mobility is a key attribute for maintaining physical stability. 15,20,21 In addition, some polymers have the ability to stabilize supersaturated aqueous drug concentrations, resulting in higher absorption potential (i.e., drug activity) relative to the crystalline form. 22,23 The maximum supersaturated concentration achievable is a function of the drug properties (i.e., chemical potential of the solid form) 24 and is represented in solution by the point at which amorphous phase separation occurs, termed liquid-liquid phase separation (LLPS).…”
Section: Introductionmentioning
confidence: 99%